Evaluation of the association between dyslipidemia and hypertensive disorder of pregnancy: a nested case control study - Varghese, Sarin; Sam, Dibu; Abraham, Anuja; Abraham, Kavitha; N., Preethi R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive disorders of pregnancy are an elusive group of diseases with multifactorial etiopathologies and varied manifestation. Abnormal pre pregnancy lipid profile is shown to have a positive correlation with endothelial dysfunction which in turn leads to development of hypertensive disorder of pregnancy. Methods: A total of 222 pregnant women who were aged between 18-35 years, with no obstetric and medical risk factors and less than 16 weeks of gestation who gave informed written consent were recruited for the study. Their baseline demographics and fasting blood samples were collected, blood samples were centrifuged, and serum was stored at -80-degree celsius. Patients were followed up till delivery and those with hypertensive disorders in pregnancy (n=22) was identified, defined as case. Control was selected after matching for body mass index and frozen serum samples were analyzed. Results: Overall incidence of hypertensive disorders in pregnancy in the study group was 12.4%. The mean early trimester fasting lipid values were higher in patients who developed hypertensive disorders, difference in mean between cases and controls was TC - 16.25 mg/dl (p-0.061), TGL- 21.45 mg/dl (p-0.143), LDL- 2.4 mg/dl (p-0.82) and for HDL 4.55 mg/dl (p-0.25). However, on stratification of early trimester fasting lipid level based on National Cholesterol Education Program (NCEP) criteria, Total cholesterol level greater than 160 mg/dl showed an odds ratio of 12.66 (p-0). Patients with early trimester fasting total cholesterol levels greater than 160mg/dl has a higher risk of developing hypertensive disorder in pregnancy.